(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The present article intends to socialize some contributions arising from my thesis of Masters in Specific Didactics in which I have made the study of two cases of memorable professors of History of the National University of the Litoral. The intention was to inquire about the characteristics of the teaching practices of two teachers considered by their students as good; to be able to recover good teaching practices in that discipline. I will try then to synthesize this characterization from: explaining his conceptions about teaching and learning; to mention their epistemological positions that position them from the history-problem when defining the contents they teach; describe how they perform a recovery work of the discipline itself through the problematization and historical awareness and, finally, present their methodological constructions configured by working with the bibliography, with various materials and with the promotion of critical thinking in the belief that this contributes to the reflection about the teaching of historical knowledge.